EKSPLORASI PENGALAMAN MAHASISWA BAHASA INGGRIS SELAMA PROGRAM PPL: HARAPAN, TANTANGAN, DAN PELAJARAN - Afrianto, Afrianto; Dahnilsyah, Dahnilsyah; Supriusman, Supriusman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
This study aims to find out how these students teachers define the concept of'professional teacher' before PPL, what are their expectations before attending the PPL, whatobstacles they encounter during the PPL, and what lessons they get during the PPL program.This qualitative study involved ten students of English Language Education as participants.They were selected through purposeful random sampling technique. Data were collectedthrough semi-structured interviews, a focused group discussion, and document analysis. Thecollected data is analyzed inductively with the help of the NVivo application. The results of thestudy showed that participants had an initial concept of professional English teachers beforethey embarked on their PPL program. Their concepts are in line with the professional teacherframework as stated in Law No. 14/2005 concerning teachers and lecturers. At the same time,all participants had high expectations for the PPL program in relation to their desire to becomeprofessional teachers. Participants also reported some of the obstacles or challenges they faced during the PPL, such as the difficulty of undergoing the teaching process and feeling too muchburden from non-teaching activities during PPL. However, at the end of the PPL, all of themclaimed to be quite satisfied with the process they had gone through. They claim to have learneda lot from PPL, among them, they have increasingly understood the complexity of the tasks andresponsibilities of a teacher.